Pendampingan Pembentukkan Kelompk Usaha Bersama (KUB) dan Penyuluhan Strategi Pemasaran Pada UMKM Kelurahan Dadapsari - Emaya Kurniawati; Adijati Utaminingsih; Widjaksono R Hartoto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program that we will carry out for MSMEs in the Dadapsari Village,North Semarang District with the target audience for business actors in the Dadapsari Village. The main problem is that so far KUB has not been formed and they do not know about the importance of a marketingstrategyIn carrying out this service the method used is assistance in making KUB and counseling aboutmarketing and promotion strategies so that the products produced by UMKM in the Dadapsari Village,Semarang District can be better known by the wider community.. The purpose of this service activity is the formation of KUB and to provide knowledge andtraining on marketing and promotionKeywords: marketing, promotion, KUB